Diagnostic value/performance of radiological liver imaging during chemoterapy for gastrointestinal malignancy: a critical review - Reginelli, Alfonso; Vacca, Giovanna; Zanaletti, Nicoletta; Troiani, Teresa; Natella, Raffaele; Maggialetti, Nicola; Palumbo, Pierpaolo; Giovagnoni, Andrea; Ciardiello, Fortunato; Cappabianca, Salvatore (Acta Biomedica Atenei Parmensis, 2019)
This article reviews the main toxic effect, complications and relative imaging findings of the liver that may appear during the oncologic follow up among patients affected by gastrointestinal malignancy. Awareness of the causative chemotherapeutic agent and regimens, pathophysiology and relative characteristic imaging findings of hepatic injuries is critical in order to obtain an accurate diagnosis especially when these parenchymal lesions are focal. An accurate synergic radiological diagnosis with Computed Tomography (CT) and Magnetic Resonance (MR) techniques may induce a potential termination of ineffective/toxic chemotherapy during early phases of treatment, changing the therapeutic plan in order to avoid first unnecessary liver biopsy and then invasive treatment as hepatic resection if not required.